Building an Inclusive Education for Autistic Children - Fitriyani, Fitriyani; Haryono, Silvester (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to find out inclusive education in schools, especially for schools that are not designated as inclusive schools but there is cooperation with teachers or schools and the government's attention to services for children with disabilities, especially for autistic children to improve communication, social interaction of autistic children with the environment at school. The type of research used is qualitative descriptive with the type of case study research. The subjects in this study are teachers who teach and children with autism who attend inclusive schools, precisely at ABBAKIDS Elementary School, Cipondoh Tangerang. The results of the study show that an inclusive educational environment must be supported by collaboration between parents, teachers, the school environment and also the role of the government that can support and be able to provide a sense of affection, understanding, empathy, and patience in communicating with children with autism. This is done as an effort to increase the sense of confidence and desire to blend in with children with autism with the surrounding environment.